ALTERATIONS IN HEMATOLOGICAL, IMMUNOLOGICAL AND BIOCHEMICAL PARAMETERS OF TENCH, TINCA TINCA AFTER ACUTE ZINC EXPOSURE - M. B. Ergönül; A. Altinda; S. Atasaun; S. L. Shah; P. Karacakaya (Journal of Animal and Plant Sciences, 2018)
There has been an increasing ecological and global public health concern associated with zinc (Zn) pollution in aquatic habitats. Zinc is deposited mainly in aquatic sediments through adsorption and precipitation. Thus, benthic fish such as tench ( Tinca tinca) are more vulnerable to Zn pollution. The present study was conducted to investigate the effects of acute high levels of Zn (20 mg/L for 24 hours) on the hematological, immunological and biochemical parameters of tench. It was found that clotting time ( CT) , thrombocyte count (TC), hemoglobin ( Hb), sedimentation rate ( SR), plasma total proteins, albumin and ceruloplasmin levels did not show any significant alterations. However, there was a significant increase in red blood cell ( RBC) counts, hematocrit (Hct), plasma glucose and plasma lactate levels; and a sharp decrease in white blood cell (WBC) count and leucocrit ( Lct) levels. The results of this study clearly indicate that, tench can be used as a responsive fish for monitoring the effects of zinc. heavy metal pollution and environmental degradation
Keywords: Zinc; tench; heavy metal; blood; fish; indicator; hematology.